A new dual-mode maximum power point tracking algorithm based on the Perturb and Observe algorithm used on solar energy system. (1st November 2018) - Ghamrawi, Ahmad; Gaubert, Jean-Paul; Mehdi, Driss
Highlights: A new dual-mode maximum power point tracking algorithm is proposed. It prevents the operating point from diverging during fast solar irradiation change. Its implementation is simple and low cost. It has been tested by simulations and experimentally. The extracted energy and the efficiency of the system are increased. Abstract: In this paper we present a new maximum power point tracking algorithm based on a modified Perturb and Observe (P&O) algorithm. The proposed algorithm is a dual mode one, the switching between the two modes is based on the value of the derivative of the power with respect to the voltage at the output of the solar panel, which must be null at the maximum power point. The first mode, a conventional P&O is active when the value of the derivative is smaller than a threshold, when its value surpasses the threshold, the second mode is activated, which prevents the voltage at the output of the solar panel to get far away from the maximum power point voltage ( V mpp ). The implementation of the proposed algorithm is very simple, similarly to the P&O, it needs just two sensors, one dedicated for the current and the second for the voltage. In comparison with the P&O, this algorithm has better performance without increasing the implementation cost. The proposed algorithm is tested by simulations using Simulink/Matlab™ to control a boost converter supplying a resistive load R. In order to further test the proposed algorithm, experimental results are presented to prove its effectiveness. The results are compared to those given by the P&O algorithm. Simulation and experimental results show that the proposed algorithm prevents the divergence of the operating point, and has a smaller response time which allows to extract more power and to decrease the losses on the adaptation stage of the solar energy system.